The Effect of Esg Disclosure on Firm Value: (Empirical Study on Companies Listed in the IDX ESG Leader Index for the Period 2021–2023) - Aditya, Meisha; Hasnawati, Sri (LPPPIPublishing, 2025)
The escalating threat of climate change has increasingly urged humanity to incorporate environmental considerations into various aspects of life, including investment decisions. This research investigates the influence of Environmental, Social, and Governance (ESG) disclosure on firm value among companies listed in the IDX ESG Leaders index during the period 2021–2023, utilizing stakeholder theory as the theoretical foundation. Employing a quantitative research design with purposive sampling, the study applies multiple linear regression analysis. The dependent variable, firm value, is proxied by the Price to Book Value (PBV), while the independent variables include aggregate ESG, Environmental, Social, and Governance disclosures, each measured using the Sustainability Report Disclosure Index (SRDI). The empirical findings reveal that aggregate ESG disclosure exerts a positive and statistically significant influence on firm value. Among the ESG components, Social Disclosure emerges as the only dimension with a significant and positive effect on firm value, whereas Environmental and Governance disclosures do not demonstrate any significant impact. These outcomes reflect the extent of investor confidence in firms that prioritize stakeholder engagement through robust ESG practices, particularly in social dimensions, thereby establishing a source of competitive advantage and enhancing firm valuation. This study offers practical implications for both corporate actors and investors by highlighting the strategic value of adopting ESG principles as non-financial instruments to support value creation and sustainable business growth.